Analisis Semiotika Ferdinand De Saurre Pesan Dakwah Pada Film “Mengejar Surga” - Tanzilal; Razzaq, Abdur; Manalullaili (Pubmedia Social Sciences and Humanities, 2024)
This research is entitled "Semiotic Analysis of Ferninanda De Saussurre's Da'wah Message in the Film Chasing Heaven". This research is motivated by da'wah which is one of the efforts to broadcast Islam. Da'wah is an obligation for every Muslim, in this modern era da'i must be creative in choosing media and be able to utilize technology so that the message they want to convey to mad'u can be well received. In this research, the media is the film "Menjejar Surga which contains preaching messages about struggle, prayer, endeavor and death. This type of research is descriptive qualitative using content analysis techniques. This research is also based on theory. Ferdinand De Saussure's semiotics is the concept of signifier and signified. The results of this research answered the problems above, we found several preaching messages, namely about marriage guardians, death and endeavors.